The Clinch and the Crack: Rupture and Resolution in Third Theatre’s Laboratory Practices - Patrick Campbell; Jane Turner (Arts, 2022)
This article maps out our critical engagement with the Third Theatre community pre- and post-COVID-19, with a focus on both performer training and the concrete material ways in which group theatres connected to this small tradition have responded to the challenges of the global pandemic. To illustrate our arguments, we draw on the Japanese craft of kintsugi—the transformative repair of ceramics—as a dispositif, employed to investigate the ways in which theatrical practice can comprise ‘an art of precious scars’, to paraphrase Stephano Carnazzi. This model allows for breaking with form and, importantly, re-modelling energy, which conversely becomes the most important aspect of the theatre laboratory, encompassing the relationships between body and form, individual and group, and artist and the wider society, importantly allowing for the creation of something that is more unique and authentic. Theatrical practice can thus be a clinch (bound like in a mother’s embrace) or jolted through disruption (like the cracks of kintsugi). Importantly, this disruption and its resolution takes place on both a level of form (as in the theatrical exercise) and on a broader, socio-political and economic plain. The article importantly focuses on both phenomena, and in so doing reflects on both the legacy and futurity of the transnational Third Theatre community.